Pendidikan Dayah di Aceh dalam Bayang-bayang Pandemi Covid-19 - Abidah Marzuki; Ahmad Khusairi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2021)
Dayah as an Islamic educational institution has a great influence on the lives of the people of Aceh in particular and Indonesia to date. People still pay great attention to dayah as an alternative education. In general, dayah education aims to foster people to have good personalities following Islamic teachings and instil a religious sense in all aspects of life. This study aims to look at the role of the dayah during the covid-19 pandemic (a case study in the Istiqamatuddin dayah in Lamceu Village, Aceh Besar). The type of research determined is descriptive qualitative using interviews and observations of educational activities in dayah during the Covid-19 pandemic. The results showed that the learning process at the dayah continued as usual but by implementing strict health protocols (prokes). Bandongan and sorogan methods are methods used in the learning process. This is done to increase the motivation and interest of the students in studying at the dayah. In addition, studying at the dayah for santri helps them prevent boredom of studying online at home during the pandemic